Uluslararası pazarlamada dağıtım kanallarının yapılandırılmasında acentelerin önemi ve bir araştırma - Özer, Alihan (My University, 2009)
A RESEARCH ON THE IMPORTANCE OF AGENCIES IN THE STRUCTURING OF DISTRIBUTION CHANNEL IN INTERNATIONAL MARKETING In recent years, the industrial and technological developments, the progress made in communications and transportation areas and the decrease in the commercial bounderies have paved the way for new oppurtunities and led an increase production in the international markets. However, the increase in production can only be valuable only if the products are brought to the consumers in the right place at the right time. The intermediary agents acting inside the distribution channels assume this task. In other words, the intermediaries act as stabilizers between production and consumption. Therefore, the role of the intermediary agents that bring the products to the consumer in the right place at the right time inside the distribution channels is of atmost importance. The aim of this thesis is to analyse the important role of intermediaries in the strucuring of distribution channels in international marketing. ULUSLARARASI PAZARLAMADA DAĞITM KANALLARININ YAPILANDIRILMASINDA ACENTELERİN ÖNEMİ ve BİR ARAŞTIRMA Son yıllarda meydana gelen sanayileşme ve teknolojik gelişmeler, haberleşme ve taşımacılıktaki gelişmeler ve ticari engellerin kırılmaya başlaması ile yeni fırsatlar ortaya çıkmış ve hem ulusal hem de uluslararası pazarlarda üretim artışlarına neden olmuştur. Fakat bu üretim artışlarının bir anlam ifade edebilmesi için üretilen ürünlerin doğru yerde ve doğru zamanda tüketicilere sunulması gerekmektedir. Bu sunma işlemini dağıtım kanalı içerisinde aracılar üstlenmektedir. Dolayısı ile üretim ve tüketim arasındaki dengeleyici unsur aracılar olmaktadır. Bu sebepten ürünlerin doğru yerde ve doğru zamanda tüketicilere ulaştırılmasını sağlayan dağıtım kanalları ve aracılar ayrı bir öneme sahiptir. Bu tez çalışmasının amacı, uluslararası pazarlamada dağıtım kanallarının yapılandırılması içerisinde aracıların öneminin incelenmesidir.
Keywords: Acente; Uluslararası Pazarlama; Üretim Yönetimi